2021
DOI: 10.1111/jopr.13339
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of 3D Printed and Prefabricated Denture Teeth Opposing Zirconia

Abstract: Purpose To evaluate the wear resistance of a recently developed three‐dimensional (3D) printed denture teeth resin compared to three commercially available prefabricated denture teeth. Materials and Methods A total of 88 maxillary first molar denture teeth were evaluated: C (Classic; Dentsply Sirona, York, PA), DCL (SR Postaris DCL; Ivoclar Vivadent, Schaan, Liechtenstein), IPN (Portrait IPN; Dentsply Sirona, York, PA), and F (Denture Teeth A2 Resin 1 L; Formlabs, Somerville, MA). The 3D printed denture tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…24 32 It was reported that printed object with SLA technology showed advantages, good mechanical resistance compared with DLP printed object. 33 34 In a previous study done by Pham et al 23 have investigated the abrasion resistance of 3D-printed denture teeth (FormLabs Resin) in comparison with conventional prefabricated denture teeth and stated that 3D-printed resin exhibited superior abrasion resistance in similarity with findings of the current study. SEM findings proved strength of FormLabs resin; based on SEM finding, FormLabs resin showed less distractive characteristics (crushed, cracks, voids, and microbubbles).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…24 32 It was reported that printed object with SLA technology showed advantages, good mechanical resistance compared with DLP printed object. 33 34 In a previous study done by Pham et al 23 have investigated the abrasion resistance of 3D-printed denture teeth (FormLabs Resin) in comparison with conventional prefabricated denture teeth and stated that 3D-printed resin exhibited superior abrasion resistance in similarity with findings of the current study. SEM findings proved strength of FormLabs resin; based on SEM finding, FormLabs resin showed less distractive characteristics (crushed, cracks, voids, and microbubbles).…”
Section: Discussionsupporting
confidence: 81%
“…27 27 It was reported that prefabricated teeth exhibited high wear resistance in comparison 3D-printed resin. 10 The prefabricated teeth were processed under high pressure with different polymerization method and consist of multiple layers with different chemical and physical properties, 23 in addition to the glossy enamel mimic coating layer increasing the wear resistance of prefabricated one as this layer was missing in 3D-printed resins. 10 In this study, 3D-printed resins were comparable to prefabricated teeth; however, the FormLab showed the highest wear resistance (lowest volume loss) value when compared with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study reported that 3D printed PMMA denture teeth exhibited a statistically lower depth of wear compared to the prefabricated PMMA resin denture teeth after 200,000 cycles of simulated chewing. 22 Based on the results of these previous studies 9 22 and our study, 3D printed resin materials are considered to have equivalent or superior wear resistance compared to the conventional PMMA materials. 9 22 …”
Section: Discussionmentioning
confidence: 91%
“…Although in laboratory studies the wear resistance of the 3D-printed artificial teeth seem to be at least adequate for denture use, long duration randomized clinical trials are necessary for in depth evaluation of this aspect as well [63,64]. Regarding other mechanical properties, CDs produced with the subtractive method have been found to be superior in toughness and surface roughness than the 3D-printed ones [65].…”
Section: Comparing the Additive Vs The Subtractive Methodsmentioning
confidence: 99%